Assessing the impact of COVID-19 on women and men in Kaduna and Cross River states of Nigeria - Alvi, Muzna; Gupta, Shweta; Barooah, Prapti (International Food Policy Research Institute, 2022)
The study was conducted in Kaduna State and Cross River State in Nigeria. It was designed as a longitudinal panel study with five rounds of data collection. The study used primary quantitative data collected using structured questionnaires administered through phone-based surveys. The study sample was drawn using systematic random sampling from an earlier in-person survey conducted by IFPRI for the Agro Processing, Productivity Enhancement and Livelihood Improvement Support’ (APPEALS) project. Figure 1 provides a detailed description on the study timeline and sample size covered in each round.